Physicochemical Parameters of Borehole Water, Tap Water and Well Water from Dawakin Kudu Local Government Area of Kano State, Nigeria - Idris, Abdullahi Mustaph; Abubakar, Musa Yahaya; Mohammad, Haladu; Muhammad, Shittu Abubakar; Mathew, Twan Sale; Adam, Ansar Bilyamin (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
Quality water is very important for maintenance of healthy environment, to determine the safety of the water consumed in the environment, pH, Turbidity, electrical conductivity, Alkalinity and hardness of water samples borehole, tap and well were analyzed. The result of the study showed that the pH of the water samples were found to be 6.3borehole, 6.7 tap and 6.8 well water, Turbidity were found to be 0 borehole, 1 tap and 0(NTU) well water, while conductivity were found to be 401 borehole, 635 tap and 556(µS/cm), well water and Hardness were found to be 172borehole, 68 tap and 88 mg/ml well water . The physicochemical analysis carried out the pH of the water were found to be from 6.3 to 6.8 only two of the samples are below the ranges laid down by W.H.O which are sample A and D and in conductivity also two of the samples are above the limit which are sample B and C and for the total hardness all are below the permissible limit by the standard (W.H.O).